Badania nowego sposobu krojenia bloków ksiażkowych nożem krążkowym ustawionym z mimośrodem - Petriaszwili, G.; Komarov, S.; Khadzhynova, S. (ТОВ «Видавництво Ліра-К», 2025)
The paper considers continuous cutting of books on automatic lines using disk knives. Research into the kinematics of cutting is conducted. The dynamic nature of the impact of the knife blade on the paper increases the efficiency of the processing process, reduces the cutting force and helps to reduce the temperature in the cutting zone.
Keywords: continuous cutting of books; disk knive